Chemical Compositions and Antioxidant Activity of Volatile Oils from Morinda citrifolia and Beta vulgaris Leaves from Nigeria - Adesegun Olusimba Onanuga; Ejike Onwudiegwu Okpala (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2022)
Morinda citrifolia L. and Beta Vulgaris L leaves are both ethnomedicinal use for the treatment of arthritis, indigestion and skin infections with no reports on their essential oils compositions. The colourless volatile oils with a percentage yield of 0.6 and 0.4 (w/w) for Morinda citrifolia L. and Beta Vulgaris L respectively were obtained. Forty-five compounds representing 94.31 % of the total percentage compositions were identified in the leaf essential oil of M. citrifolia with the most abundant compound as 14-beta-H-pregna- (33.13%). Forty-eight compounds representing 74.18% of the total oil composition were identified in the leaf oil of B. Vulgaris with phytol (24.20%) as the dominant compound. The essential oils showed good free radical scavenging activity when compared to ascorbic acid used as control, with % inhibition varying from 88.74 ± 0.010 to 96.61 ± 0.004 as compared to 95.68 ± 0.010 to 97.31±0.003 of the ascorbic acid at (100 to 6.25 mg/ml) concentrations. The leaves essential oils of Morinda citrifolia L. and Beta Vulgaris L contains chemical compounds that might be responsible for their antioxidant activity. This result validates the traditional usage of these plants in the treatment of arthritis, indigestion and skin infections.